Invitation to the Concert of the rectors - Technische Hochschule Karlsruhe (1923)
Invitation to the Concert of the rectors, at Karlsruhe Technical University, June 1923. In December 1922 Georg Bredig (1868-1944) became the Rector at Karlsruhe. The back of the invitation includes handwritten notes by Bredig.
Keywords: Invitation cards; Bredig, Georg, 1868-1944; Technische Hochschule Karlsruhe; Concerts